2013
DOI: 10.1155/2013/503421
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Is Associated with Survival in Patients with Brain Metastasis: A Preliminary Report

Abstract: Impaired heart rate variability (HRV) has been demonstrated as a negative survival prognosticator in various diseases. We conducted this prospective study to evaluate how HRV affects brain metastasis (BM) patients. Fifty-one BM patients who had not undergone previous brain operation or radiotherapy (RT) were recruited from January 2010 to July 2012, and 40 patients were included in the final analysis. A 5-minute electrocardiogram was obtained before whole brain radiotherapy. Time domain indices of HRV were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 27 publications
1
43
1
Order By: Relevance
“… Guo et al (2015) , demonstrated with 24-h ECG monitoring a significantly lower survival rate in patients with SDNN < 70 ms compared to patients with SDNN > 70 ms. The same conclusion, i.e., lower SDNN associated with lower survival, was reached in the studies of Fadul et al (2010) , Kim et al (2010) , Wang et al (2013) , and also De Couck et al (2016) . Chiang et al (2013) , investigated a group of patients in a palliative care setting in their last weeks of life, although a much shorter ECG time frame (10 s to 5 min ECGs) was applied.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“… Guo et al (2015) , demonstrated with 24-h ECG monitoring a significantly lower survival rate in patients with SDNN < 70 ms compared to patients with SDNN > 70 ms. The same conclusion, i.e., lower SDNN associated with lower survival, was reached in the studies of Fadul et al (2010) , Kim et al (2010) , Wang et al (2013) , and also De Couck et al (2016) . Chiang et al (2013) , investigated a group of patients in a palliative care setting in their last weeks of life, although a much shorter ECG time frame (10 s to 5 min ECGs) was applied.…”
Section: Resultssupporting
confidence: 73%
“…Irrespective of the HRV measurement duration and variables, all studies showed a reduced HRV in the groups with more severely affected disease. Wang et al (2013) and De Couck et al (2016) evaluated the difference of patients with advanced stages compared to patients with primary and secondary stages as well as compared to healthy individuals. They reported that disease severity affects HRV, as patients in early stages showed a significantly higher vagal nerve activity than patients in later stages.…”
Section: Resultsmentioning
confidence: 99%
“…Infact, autonomic dysfunction is now a day is considered as a non-invasive prognostic marker for chemotherapeutic regime [ 18 ]. HRV is a clinical marker of autonomic function and cancer patients with low HRV are associated with increased cardiovascular risk [ 19 ]. Treatment with ALA helped to restore the autonomic control and therefore, could be designated to have good prognostic value in chemoprevention regime as proposed through ALA (Table 1 , Supplementary Table 1 and Supplementary Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Search History in Pubmed: Using the words HRV heart cancer survival, 17 studies were found, of whom De Couck 2016 [ 33 ]; Kim 2015 [ 34 ]; Giese-Davis 2015 [ 35 ]; Wang 2013 [ 36 ] De Couck 2013 [ 37 ]; Chiang 2013 [ 38 ]; Kim 2010 [ 39 ]; and Fadul 2010 [ 40 ] were eligible. Using the words HRV heart cancer prognosis, 14 studies were found: 1 new one: Mouton 2012 [ 41 ].…”
Section: Methodological Evaluation Of Studiesmentioning
confidence: 99%